Mike Meyers' CompTIA Network+ guide to managing and troubleshooting networks lab manual (Exam N10-008) - Meyers, Mike, 1961-; Weissman, Jonathan S. (McGraw-Hill Education, 2022)
Practice essential IT skills and prepare for the 2021 version of the CompTIA Network+ exam This thoroughly revised lab manual challenges you to solve real-world problems by learning to successfully apply the techniques contained in Mike Meyers' CompTIA Network+ Guide to Managing and Troubleshooting Networks, Sixth Edition. Clear, measurable lab objectives map directly to every topic on the test, enabling readers to pass the challenging exam with ease. Mike Meyers' CompTIA Network+ Guide to Managing and Troubleshooting Networks Lab Manual, Sixth Edition (Exam N10-008) contains more than 90 hands-on labs along with materials lists, lab setup details, and step-by-step instructions that require you to think critically. The book features special design elements that teach and reinforce retention. You will Lab Analysis questions and a Key Term Quiz that helps to build vocabulary. Contains 90+ hands-on labs with clear objectives and instructions Includes a 10% discount voucher coupon for the exam, a $32 value Lab solutions are not printed in the book and are only available to adopting instructors Publisher's Note: Products purchased from Third Party sellers are not guaranteed by the publisher for quality, authenticity, or access to any online entitlements included with the product.